2013
DOI: 10.1007/s12272-013-0175-6
|View full text |Cite
|
Sign up to set email alerts
|

Docetaxel-loaded thermosensitive liquid suppository: optimization of rheological properties

Abstract: The main purpose of this work was to optimize the rheological properties of docetaxel (DCT)-loaded thermosensitive liquid suppositories for rectal administration. DCT-loaded liquid suppositories were prepared by a cold method and characterized in terms of physicochemical and viscoelastic properties. Major formulation parameters including poloxamer (P407) and Tween 80 were optimized to adjust the thermogelling and mucoadhesive properties for rectal administration. Notably, the gel strength and mucoadhesive forc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 33 publications
1
23
1
Order By: Relevance
“…12 In brief, a weighed quantity of liquid suppository was placed in a glass vial which was in turn placed in an automated water bath containing a magnetic stirrer and a digital thermometer. A magnetic bar was allowed to rotate (~100 rpm) in the liquid suppository and the temperature was gradually increased from 20°C to 40°C at a rate of 1°C.…”
Section: Viscoelastic Property Gelation Temperaturementioning
confidence: 99%
See 4 more Smart Citations
“…12 In brief, a weighed quantity of liquid suppository was placed in a glass vial which was in turn placed in an automated water bath containing a magnetic stirrer and a digital thermometer. A magnetic bar was allowed to rotate (~100 rpm) in the liquid suppository and the temperature was gradually increased from 20°C to 40°C at a rate of 1°C.…”
Section: Viscoelastic Property Gelation Temperaturementioning
confidence: 99%
“…Recently, various process and formulation related variables were optimized in order to adjust the thermogelling and mucoadhesive properties for effective rectal administration (Table 1). 12 The rate and extent of nanoparticle internalization is highly dependent on the particle size and size distribution of DCT-loaded nanomicelles. In this regard, results of dynamic light scattering analysis showed that micelles were nanosized with an average size around ~15 nm with a narrow poly dispersity index (0.2) (Figure 2A).…”
Section: Physicochemical Characterization Of Dct-loaded Nanomicellesmentioning
confidence: 99%
See 3 more Smart Citations